The priority of istima' skills in arabic learning - Muhammad Syafii Tampubolon; Rahmad Ilahi (Yayasan Azhar Amanaa Yogyakarta, 2024)
Istima' is a very important activity in our lives, and a means for the first time in human life to be able to reach the stage of good community interaction. This research is a library research, which examines various books and the results of previous research that discuss the same theme to obtain a theoretical basis for the problem under study. The objective of Istima' learning is to enrich children's vocabulary so that it helps students when learning to read and write. The istima lesson' is considered by most teachers to not need to be taught because it is already implicit in the other three components of language skills. The urgency of learning istima' skills before other language skills can be observed from the process of language development in children before they can read and write, they can speak first, what they talk about, of course not deviate from what they listen to everyday.